Green Financial Management as a Strategy to Face the Challenges of Sustainable Finance - Wenno, Meiske; Faisal, Muhammad; Regar, Erfendi; Arifin, Hasmia Melati (West Science Business and Management, 2025)
This study examines green finance management as a strategic approach to addressing sustainable finance challenges in Indonesia. As the country faces pressing environmental and social issues, financial institutions are under increasing pressure to align their practices with sustainability principles. Despite policy initiatives such as the OJK Sustainable Finance Roadmap, challenges remain in regulatory enforcement, institutional capacity, and public awareness. Using a qualitative design, data were collected through in-depth interviews with three key informants representing a financial institution, a regulatory body, and a sustainability practitioner. The findings highlight five central themes: the importance of strengthening regulatory frameworks, enhancing institutional capacity, promoting stakeholder collaboration, overcoming awareness and cultural barriers, and fostering green financial innovation. These results suggest that green finance management serves as both a policy instrument and a practical tool for aligning economic growth with environmental protection. The study contributes to the literature on sustainable finance in Indonesia and offers practical insights for policymakers, financial institutions, and stakeholders in advancing sustainability through finance.